Anti‐Osteoporosis Medication Prescriptions and Incidence of Subsequent Fracture Among Primary Hip Fracture Patients in England and Wales: An Interrupted Time‐Series Analysis. (4th July 2016) - Hawley, Samuel; Leal, Jose; Delmestri, Antonella; Prieto‐Alhambra, Daniel; Arden, Nigel K; Cooper, Cyrus; Javaid, M Kassim; Judge, Andrew; ,
ABSTRACT: In January 2005, the National Institute for Health and Care Excellence (NICE) in England and Wales provided new guidance on the use of antiosteoporosis therapies for the secondary prevention of osteoporotic fractures. This was shortly followed in the same year by market authorization of a generic form of alendronic acid within the UK. We here set out to estimate the actual practice impact of these events among hip fracture patients in terms of antiosteoporosis medication prescribing and subsequent fracture incidence using primary care data (Clinical Practice Research Datalink) from 1999 to 2013. Changes in level and trend of prescribing and subsequent fracture following publication of NICE guidance and availability of generic alendronic acid were estimated using an interrupted time series analysis. Both events were considered in combination within a 1‐year "intervention period." We identified 10, 873 primary hip fracture patients between April 1999 and Sept 2012. Taking into account prior trend, the intervention period was associated with an immediate absolute increase of 14.9% (95% CI, 10.9 to 18.9) for incident antiosteoporosis prescriptions and a significant and clinically important reduction in subsequent major and subsequent hip fracture: –0.19% (95% CI, –0.28 to –0.09) and –0.17% (95% CI, –0.26 to –0.09) per 6 months, respectively. This equated to an approximate 14% (major) and 22% (hip) reduction at 3 years postintervention relative to expected values based solely on preintervention level and trend. We conclude that among hip fracture patients, publication of NICE guidance and availability of generic alendronic acid was temporally associated with increased prescribing and a significant decline in subsequent fractures. © 2016 American Society for Bone and Mineral Research.